COMPARATIVE STUDY OF THE IMPACT OF BHAGAVAD GITA PHILOSOPHY ON PERSONAL VALUES ​​OF STUDENTS - Sharma, Geetika; Sharaf, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Bhagavad Gita is a source of profound spiritual knowledge and moral guidance. This research studies its impact on the personal values ​​of students, focusing on key principles such as ethics, self-discipline, and social responsibility. This study compares the values ​​of students familiar with and unfamiliar with the teaching of the Gita to understand how the influence of the Gita shapes their personal and social values.